The styles of coping with stress in women with normal and highly compromised pregnancy - Rutkowska, Aleksandra; Rolińska, Agnieszka; Kwaśniewski, Wojciech; Makara-Studzińska, Marta; Kwaśniewska, Anna (Current Problems of Psychiatry, 2011)
Introduction: Compromised pregnancy is a source of a lot of negative emotions for a woman, especially if it makes hospitalization necessary, which may cause stress and unfavorably influence the treatment process. The subject of the study was defining the styles of coping with stress in women with compromised and normal pregnancy. Material: The study was conducted in a group of 111 women in the period from March 2008 to January 2010. The criteria according to which patients were included in the study were the following: 1) primipara; 2) the stage of pregnancy – up to the 32nd week. The study group: 61 women hospitalized at the Obstetrics and Compromised Pregnancy Clinic of the Lublin Medical University with an abnormal, pathological course of pregnancy. The control group: 50 women with a normal course of pregnancy. All the women were about 28 years old and came from Lublin or the vicinity; they were mostly married, with higher or secondary education. Methods: In order to define and compare the preferred styles of coping with stress in both groups the Coping in Stress Situations Questionnaire (CISS) was used. Results: The preferred style of coping in both groups was the TOS (task-oriented style). No statistically significant difference was found between the groups. The second most frequent style of coping was the AOS (avoidance-oriented style) – here a statistical difference was found in a component of this style, that is ESA (engaging in substitute activities), at the level of tendency p=(0.09), to the advantage of the studied group, which means that the patients hospitalized at the Obstetrics and Compromised Pregnancy Clinic more often than the ones with normal pregnancy avoided confrontation with the difficult situation by engaging in activities other than concentrating on the problem. The next (with respect to the level of results of raw averages) style in both groups was the EOS (emotion-oriented style). Here no statistically significant differences between the groups were found. Discussion of the results: In both studied groups the women choose the style oriented to the task almost as frequently as the style oriented to avoidance. This may prove emotional ambivalence in pregnant women. In the group of women hospitalized because of a threat to the pregnancy, the tendency occurs to escape the problem by engaging in substitute activities. Conclusions: 1. Compromised pregnancy does not significantly influence the women’s confrontation with the stress situation. 2. The fact of hospitalization in a highly compromised pregnancy may have influence on a lessening of the tendency to confront the stress-inducing situation and intensification of escape reactions by engaging in substitute activities.